1978
DOI: 10.1111/j.1464-410x.1978.tb06208.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of the Results of Transurethral Resection of the Prostate

Abstract: In a review of 1057 consecutive prostatectomies of which 95% were performed transurethrally, carcinoma was present in 11.8%. There were 10 deaths within a month of operation (0.9%), 9 of these patients having been exceptionally old and unfit. The rate of complications and the end results appear to justify using transurethral resection as the method of choice for prostatectomy whenever it is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
1
4

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 7 publications
9
45
1
4
Order By: Relevance
“…It is not possible to validate this subjective outcome of therapy, the prognostic value of diÂerent diagnostic tests is low [11][12][13][14]. The subjective the accuracy of the medical decisions recorded using the computer program; there is an intrinsic accuracy primaroutcome after TURP has a probability of about 0.8 for improvement or complete recovery and this probability ily because the decision-maker only receives the 'hard' objective data from each case and thus the method could does not seem to be related to the diagnostic process, which diÂered in the studies reported [15][16][17][18]. Thus, if be useful in studying the reproducibility of medical decisions made using diagnostic data.…”
Section: Resultsmentioning
confidence: 99%
“…It is not possible to validate this subjective outcome of therapy, the prognostic value of diÂerent diagnostic tests is low [11][12][13][14]. The subjective the accuracy of the medical decisions recorded using the computer program; there is an intrinsic accuracy primaroutcome after TURP has a probability of about 0.8 for improvement or complete recovery and this probability ily because the decision-maker only receives the 'hard' objective data from each case and thus the method could does not seem to be related to the diagnostic process, which diÂered in the studies reported [15][16][17][18]. Thus, if be useful in studying the reproducibility of medical decisions made using diagnostic data.…”
Section: Resultsmentioning
confidence: 99%
“…The early mortality rate from TURP is about 1.6% vs. a mortality rate of about 1% for open surgery [7, 8, 9]. Our experience shows a perioperative mortality of about 0.5%, vs. a mortality rate of 0.4% nationwide.…”
Section: Resultsmentioning
confidence: 85%
“…Marshall [10]reports that 15–20% of the patients who underwent open surgery needed blood transfusion vs. 3–16% of those patients who underwent TURP [7, 8, 9, 10, 11]. The data on hemorrhage in Italian urologic units show that this appears to be around 6% (range 0.1–45%).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, TURP is described as being inferior to open prostatectomy with regard to urine flow, residual urine volume, etc. Complete resection of the adenoma beyond the verumontanum is preferable in the long-term perspective of preventing recurrence and the verumontanum should not been a landmark for TURP [9].…”
Section: Discussionmentioning
confidence: 99%